Effect of Three Types of Temporary Luting Cements and Abutment Surface Sandblasting on Retentive Strength of Implant-Supported Fixed Prostheses - Shojaedin Shayegh; Ali mohammad Salari; Mohsen Ayoubi; Farzan Younesi (Islamic Dental Association of Iran, 2015)
Background and Aim: Achieving appropriate retention and easy retrieva bility at the same time is challenging in implant-supported fixed par tial dentures (FPDs). Researchers have always been in search of a temporary cement to improve the retentive strength. The aim of this in vitro study was to evaluate the effect of three different temporary ce ments and sandblasting of the abutment surface on the retentive strength of implant- supported fixed prostheses. Materials and Methods: In this experimental study, 10 DIO implant analogues were mounted in acrylic resin. Twenty abutments were divided into two groups of 10. The ab-utments in groupone were used in their intact standard form while those in group two were sandblasted. Sixty metal copings were fabricated and cemented on abutmentsof each group usingthree types of temporary cements namely Kerr, Provyand GC. Specimens were subjected toa universal testing machine to measure their retentive strength.The re-sults were analyzed by two-way ANOVA and pairwise comparison was performed using-Tukey's post-hoc test. Results: The retentive strength of TempBond (Kerr) with sandblasted abutments was sig-nificantly higher than that of the other two cements (p<0.001). In standard abutments, Provy had slightly but not significantly higher retentive strength. The lowest values in both abutment groups were obtained by GC cement. Conclusion: Kerr TempBond cement with sandblasted abutments yields the highestreten-tive strength.